(3GdJShjb GdMSj (B/s - (3dNPGQj, MSfGAs; (3dMhd, SGejI s ((3GdLRGFQ (B: s (3OGQ bGfI ddfTQ hGdJhRjY (B, s, 2022)
(3jVe GdNdajI GdYdejI hGdJShjbjI ddJShjb GdMSj, GdefXheI GdYUHjI deYGdLI GdeYdheGJ GdMSjI, GdJTQjM GdYUHj hGdaSjhdhLj ddCfXeI GdMSjI, GdYdGeI GdJLGQjI GdMSjI, JWhQ GSJNOGe GdMhGS ef GdacQ GdHjhdhLj Edi GdJShjb(B.s
Keywords: (3GdJShjbs; (3GdYdGeI GdJLGQjIs; (3GdeSJgdcs